Explosives: Metal‐Organic Framework Templated Synthesis of Copper Azide as the Primary Explosive with Low Electrostatic Sensitivity and Excellent Initiation Ability (Adv. Mater. 28/2016). Issue 28 (21st July 2016) - Wang, Qianyou; Feng, Xiao; Wang, Shan; Song, Naimeng; Chen, Yifa; Tong, Wenchao; Han, Yuzhen; Yang, Li; Wang, Bo
Abstract : On page 5837, L. Yang, B. Wang, and co‐workers describe a metal–organic framework (MOF) templating method to synthesize copper azide uniformly anchored in a 3D interconnected carbon matrix and evenly spaced by the electron‐conductive joints. This strategy sheds light on the preparation of powerful yet safe primary explosives and fulfills the need for controllable explosive systems.